GnRH-mediated suppression of S100A4 expression inhibits endometrial epithelial cell proliferation in sheep via GNAI2/MAPK signaling - Jiao, Xiyao; Chu, Zhili; Li, Meng; Wang, Jiurong; Ren, Zilong; Wang, Leyang; Lu, Chengcheng; Li, Xiangyun; Ren, Feng; Wu, Xinglong (Frontiers in Veterinary Science, 2024)
Background: Gonadotrophin-releasing hormone (GnRH) administration significantly decreases the pregnancy rate of recipient ewes after embryo transfer, possibly because GnRH affects endometrial epithelial cell function. Therefore, this study investigated the effect of GnRH on endometrial epithelial cells.Methods: Transcriptome sequencing was used to determine the regulatory effect of GnRH on the ewe endometrium, and the S100A4 gene, which showed altered transcription, was screened as a candidate regulator of this effect. Endometrial epithelial cells were further isolated, the S100A4 protein was immunoprecipitated, and host proteins that interacted with S100A4 were identified by mass spectrometry.We further verified the effects of S100A4 and GNAI2 on the proliferation of endometrial epithelial cells via overexpression/knockdown experiments and subsequent CCK-8 and EdU assays. The effect of S100A4 deletion in endometrial cells on reproduction was verified in mice with S100A4 knockout.Our results showed that S100A4 gene transcription in endometrial cells was significantly inhibited after GnRH administration. GNAI2 was identified as a downstream interacting protein of S100A4, and S100A4 was confirmed to activate the MAPK signaling pathway to promote cell proliferation by targeting GNAI2.GnRH can suppress the expression of S100A4 in the endometrium, consequently inhibiting the proliferation of endometrial cells through the S100A4/GNAI2/MAPK signaling pathway. These findings suggest a potential 删除的内容: GnRH